2004
DOI: 10.1111/j.1525-1594.2004.47269.x
|View full text |Cite
|
Sign up to set email alerts
|

Impeller Behavior and Displacement of the VentrAssist Implantable Rotary Blood Pump

Abstract: The VentrAssist implantable rotary blood pump, intended for long-term ventricular assist, is under development and is currently being tested for its rotor-dynamic stability. The pump is of the centrifugal type and consists of a shaftless impeller, also acting as the rotor of the brushless DC motor. The impeller remains passively suspended in the pump cavity by hydrodynamic forces, resulting from the small clearances between the impeller outside surfaces and the pump cavity. In the older version of the pump tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Increased static force requires excessive power diversion to the bearing system, which reduces overall efficiency. Hydrodynamic bearing systems become more dynamically stable with the introduction of a static bias force (16), however, the suspension capacity is partially compromised in the direction of this force vector. Finally, the wear lifetime of mechanical type pivot bearing systems significantly benefit from a reduction in static thrust.…”
Section: Hydraulic Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Increased static force requires excessive power diversion to the bearing system, which reduces overall efficiency. Hydrodynamic bearing systems become more dynamically stable with the introduction of a static bias force (16), however, the suspension capacity is partially compromised in the direction of this force vector. Finally, the wear lifetime of mechanical type pivot bearing systems significantly benefit from a reduction in static thrust.…”
Section: Hydraulic Forcementioning
confidence: 99%
“…However, the stability of a hydrodynamic bearing system increases with the introduction of a static bias force (16). The weight of the impeller can be used; however, the bias may be increased in the desired direction with the correct impeller/volute selection.…”
Section: Relevance To Bearing Designmentioning
confidence: 99%
“…In terms of the measurement device, Chung (9) reported that the accuracy of the eddy current gap sensors could not be assured because of the interference of the electromagnetic noise from the motor coils. However, the motor of our pump was placed below the housing bottom, and far enough from the sensors, while the motor of Chung's pump was built in the rotor.…”
Section: Measurement Of the Radial Motion Of The Rotormentioning
confidence: 99%
“…Michael K.C. Chung et al (57) of the University of Technology (Sydney, Australia) reported on impeller behavior and displacement of their implantable rotary blood pump. The impeller was hydrodynamically suspended within the pump cavity and results were typical of centrifugal pump behavior.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%